Strategi Meningkatkan Nilai Produk Berbahan Mangga Melalui Pemberdayaan Masyarakat - Ria Adriyani (Dimasejati: Jurnal Pengabdian Kepada Masyarakat, 2019)
The community empowerment activities of Gemulung Village, Cirebon Regency, West Java, started from seeing the potential of natural resources available in the region to the availability of raw materials and supported by the ability of the community in groups. The Community Service Program is implemented as an effort to help the people of the village of Gemulung, Cirebon Regency, West Java. Assistance to the Gumulung village community, which is empowering mothers to utilize mangoes that would otherwise have been wasted or have no economic value with product innovation, would be a valuable additional source of income, thereby potentially increasing community welfare, through production, packaging, and marketing training activities. The target is for community groups to work together by opening a network for product distribution, assisted by the Community Service Team. As for the production, packaging, and marketing training activities help motivate the community to participate from the beginning of the production process to marketing. It is hoped that the people of Gumulung Village will be able to sell the products of the Mango Confectionery, where the business can develop so that the Mango Confectionery can become the main product of the Gumulung Village.